A unified model for cross-modal plasticity and skill acquisition - Park, Woon Ju; Fine, Ione (Frontiers in Neuroscience, 2024)
Historically, cross-modal plasticity following early blindness has been largely studied in the context of visual deprivation. However, more recently, there has been a shift in focus towards understanding cross-modal plasticity from the perspective of skill acquisition: the striking plasticity observed in early blind individuals reflects the extraordinary perceptual and cognitive challenges they solve. Here, inspired by two seminal papers on skill learning (the “cortical recycling” theory) and cross-modal plasticity (the “metamodal” hypothesis) respectively, we present a unified hypothesis of cortical specialization that describes how shared functional, algorithmic, and structural constraints might mediate both types of plasticity.